Cover Feature: Mechanistic Parameters of Electrocatalytic Water Oxidation on LiMn2O4 in Comparison to Natural Photosynthesis (ChemSusChem 22/2017). Issue 22 (14th November 2017) - Köhler, Lennart; Ebrahimizadeh Abrishami, Majid; Roddatis, Vladimir; Geppert, Janis; Risch, Marcel
Abstract : The Cover Feature shows bio‐inspired electrocatalysis for the oxygen evolution reaction on LiMn2 O4 nanocrystals. The electrocatalyst shares the cubane motif with the active site of photosystem II and the valence of Mn 3.5+ with the dark‐stable state of natural photosynthesis. These commonalities allow discussion of the electrocatalytic mechanism of LiMn2 O4 in the context of natural photosynthesis. More information can be found in the Full Paper by Köhler et al. onpage 4479 in Issue 22, 2017 (DOI:10.1002/cssc.201701582 ).